(untitled) (Fiep Bulletin - online, 2012)
The article presents the results of two studies conducted in Brazil and Portugal, where it was noted the concerns about the gap between what is presented in physical education and influences in the students’ daily lives. Studies have shown the need for are thinking of practices as well as the responsibility of teachers with these changes. It was discussed the importance of physical education in the school setting, as well as the questions related to the sport takes hegemonic role on the content. The relationship of corporal practices in school and life style and as a determining factor in quality of life of future adults was studied.